2019
DOI: 10.1093/aje/kwz178
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Exposure in the First Year of Life and the Risk of Attention-Deficit/Hyperactivity Disorder: A Population-Based Cohort Study

Abstract: Early childhood antibiotic exposure induces changes in gut microbiota reportedly associated with the development of attention-deficit/hyperactivity disorder (ADHD). We conducted a population-based cohort study to examine the association between antibiotic use in the first year of life and ADHD risk. We included children born in Manitoba, Canada, between 1998 and 2017. Exposure was defined as having filled 1 or more antibiotic prescriptions during the first year of life. ADHD diagnosis was identified in hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…13,25,29,32,61,64,76,78,93,103,109,111,115,116,121,123,148,154,176,181,182,191,195,197,198,201 Moreover, the risk of adverse long-term health outcomes is often higher for antibiotics with a broad-spectrum including cephalosporins and macrolides. 18,21,34,36,57,58,61,69,78,91,92,111,121,123,137,157,163,172,182,195,197 These findings underline the importance of antibiotic stewardship, specifically to avoid antibiotics for infections that are likely viral and to use the most narrow-spectrum antibiotic possible. 226 A recent large population-based prospective study sh...…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…13,25,29,32,61,64,76,78,93,103,109,111,115,116,121,123,148,154,176,181,182,191,195,197,198,201 Moreover, the risk of adverse long-term health outcomes is often higher for antibiotics with a broad-spectrum including cephalosporins and macrolides. 18,21,34,36,57,58,61,69,78,91,92,111,121,123,137,157,163,172,182,195,197 These findings underline the importance of antibiotic stewardship, specifically to avoid antibiotics for infections that are likely viral and to use the most narrow-spectrum antibiotic possible. 226 A recent large population-based prospective study sh...…”
Section: Discussionmentioning
confidence: 95%
“…Four studies investigated the association between antibiotic exposure and the development of attention deficit hyperactivity disorders (ADHD) in 756,348 children (25,143 cases with one study not reporting number of cases). 22,58,130,172 They evaluated children by ICD codes. All four studies evaluated antibiotic exposure before two years of age.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown conflicting results regarding exposure to antibiotics in early life and ADHD. For example, recent population-based Canadian and Danish studies 92,93 did not observe a significant association between antibiotic exposure in the first years of life and ADHD, particularly in sibling-controlled analysis that adjusted for familial confounding factors. However, a large Finnish study 94 suggested an association between exposure to antibiotics in early life and ADHD that may not be fully explained by familial confounding.…”
Section: Antibiotic Regimenmentioning
confidence: 99%